Religious Dynamics in Mass Media: A Study on Popular Articles in Kompas and Republika Newspapers - Khusairi, Abdullah; Fata, Ahmad Khoirul (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2021)
This paper examines the religious dynamics image in contemporary Indonesia was presented by the printed mass media. Using van Dijk's critical discourse analysis method, and the hierarchy of influence media content of Pamela Shoemaker and Stephen Reese, this paper examines the content of popular articles in the Kompas and Republika for the period 2013-2017. These two print media were chosen because they are two different ideological poles. Kompas was born from Catholic activists and supported by several military officers. Meanwhile, Republika was founded by Islamic activists with government support. The themes of popular articles in both media revolve around issues of the state and democracy, political dynamics and Islamic parties, and spirituality. The religious discourse contest at Kompas and Republika was filled with Muslim scholars and leaders of Islamic mass organizations. Kompas does not provide enough space for new writers so that its popular articles are filled by monotonous scholars. On the other hand, Republika has promoted many new writers. However, Republika also features internal writers. Popular articles from Kompas and Republika put forward a moderate religious face. However, Republika seems to emphasize the Islamic side more, while Kompas appears to be more inclusive.